Emergence of Carbapenem-Resistant Serotype K1 Hypervirulent Klebsiella pneumoniae Strains in China - Zhang, Rong; Lin, Dachuan; Chan, Edward Wai-Chi; Gu, Danxia; Chen, Gong-Xiang; Chen, Sheng (Antimicrobial agents and chemotherapy, 2016)
We report the emergence of five carbapenem-resistant K1 hypervirulent Klebsiella pneumoniae (hvKP) strains which caused fatal infections in hospital patients in Zhejiang Province, China, upon entry through surgical wounds. Genotyping results revealed the existence of three genetically related strains which exhibited a new sequence type, ST1797, and revealed that all strains harbored the magA and wcaG virulence genes and a plasmid-borne bla(KPC-2) gene. These findings indicate that K1 hvKP is simultaneously hypervirulent, multidrug resistant, and transmissible.